Factors Related To The Incidence Of Anemia Among Pregnant Women In The Working Area Of Kedokanbunder Public Health Center, Indramayu Regency - Fitriyani, Wisni; Ratnasari, Eka; Rahmatika, Siti Difta; Nurjanah, Nunung (Jurnal Medisci, 2025)
Background. The global prevalence of anemia. According to estimates from the World Health Organization (WHO), around 40% of children aged 6-59 months, 37% of pregnant women, and 30% of women aged 15-49 worldwide experience anemia. In Indonesia, the prevalence of iron deficiency anemia among pregnant women was 37.1% in 2020 and 24.5% in 2021. The impact of anemia on pregnant women includes significant complications for both the mother and the fetus. Based on this data, Kedokanbunder Health Center is among the health centers with the highest anemia rates in Indramayu district, affecting 104 pregnant women. Aims. This study aims to determine the relationship between the factors associated with anemia. Methods: The research design is quantitative, correlational. The population consists of pregnant women in the working area of the Kedokanbunder Community Health Center, totaling 88 individuals, and the sampling method used is Accidental Sampling. The instrument used is a questionnaire, and the data analysis techniques are univariate and bivariate, with the Chi-square test used to analyze the data. Result. The research results showed that among pregnant women, the majority (53, 60.2%) had no anemia. The Chi-square test results indicated a p-value of 0.978 for age (p > 0.05), a p-value of 0.006 for education (p < 0.05), a p-value of 0.019 for parity (p < 0.05), a p-value of 0.008 for knowledge (p < 0.05), and a p-value of 0.202 for economic status (p < 0.05). Conclusion. Based on the results, it can be concluded that there is a relationship between education, knowledge, parity, and the occurrence of anemia. There is no relationship between age and economic status with the occurrence of anemia. Implementation. It is recommended for health workers to carry out preventive measures by providing education about pregnant women through maternal classes and performing early detection of risk factors for anemia in pregnant women at Puskesmas Kedokanbunder, Indramayu regency, at 2025